Zoon's balanitis presenting as discrete polyp on glans penis - Catalina A. Palma; Peter Ferguson; Nicola Jeffery (Urology Case Reports, 2022)
The diagnosis of genital dermatological conditions in males can be challenging and rely on physical examination and biopsy. This report describes an unusual case of Zoon's balanitis producing a discrete polyp on the glans penis, in addition to the classically described well-demarcated erythematous macule.